Geriatric Rehabilitation: A Clinical Approach - Bottomley, Jennifer M.; Lewis, Carole Bernstein (Thorofare, NJ : SLACK Incorporated, 2020)
"Authors Jennifer Bottomley and Carole Lewis have compiled the plethora of available scientific research on geriatric populations and combined it with their years of actual clinical practice. Together this makes A Clinical Approach to Geriatric Rehabilitation, Fourth Edition a complete evidence-based guide to the clinical care of geriatric patients and clients. The first part of this text tackles applied gerontological concepts, providing the general knowledge base necessary for treating geriatric patients. Topics in this section include patient evaluation, an exploration of nutritional needs, and age-related changes in physiology and function, as well as many other foundational areas. In the second section, topics become more focused on patient care concepts like neurologic considerations, cardiopulmonary and cardiovascular considerations, and establishing community-based screening programs. In the final section, chapters center on administration and management, including important subjects such as attitudes, ethics, and legal topics, as well as consultation and research. Designed to provide valuable, real-life clinical knowledge in the practice of geriatric rehabilitation, A Clinical Approach to Geriatric Rehabilitation, Fourth Edition gives physical therapists an evidence-based guide to the clinical aspects of rehabilitative care in older adult patients and clients"--
Demographics of Aging -- Comparing and Contrasting the Theories of Aging -- Age-Related Changes in Physiology and Function -- Describing Psychosocial Aspects of Aging -- Pathological Manifestations of Aging -- Exploring Nutritional Needs -- Geriatric Pharmacology -- Principles and Practice of Geriatric Rehabilitation -- Patient Evaluation -- Functional Assessment -- Orthopedic Considerations -- Neurologic Considerations -- Cardiopulmonary and Cardiovascular Considerations -- Integumentary Considerations -- Establishing Community-Based Screening Programs -- Communication -- Attitudes, Ethics, and Legal Topics in Gerontology -- Education and the Older Adult: Learning, Memory, and Intelligence -- Administration of Geriatric Services -- Consultation and Research.
Preceded by Geriatric rehabilitation : a clinical approach / Carole B. Lewis, Jennifer M. Bottomley. 3rd ed. Pearson/Prentice Hall, c2008.
Includes bibliographical references and index.
Keywords: Physical therapy for older people; Rehabilitation; Aged; Aging; Geriatric Assessment; Evidence-Based Medicine